2015
DOI: 10.1186/s12957-015-0541-6
|View full text |Cite
|
Sign up to set email alerts
|

A literature review on surgery for cervical vagal schwannomas

Abstract: Cervical vagal schwannoma is a benign, slow-growing mass, often asymptomatic, with a very low lifetime risk of malignant transformation in general population, but diagnosis is still a challenge. Surgical resection is the treatment of choice even if its close relationship with nerve fibres, from which it arises, threats vagal nerve preservation. We present a case report and a systematic review of literature. All studies on surgical resection of cervical vagal schwannoma have been reviewed. Papers matching the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 24 publications
(26 reference statements)
4
66
1
2
Order By: Relevance
“…Diagnostic imaging enabled preoperative diagnosis of schwannoma in all patients; however, accurate preoperative estimation of the nerves of origin was difficult. One reason for this difficulty was the fact that neural paralysis of the involved nerve, which can be a specific subjective symptom, developed in only 1 of the 21 patients (4.8%), whereas nonspecific subjective symptoms, such as cervical mass and pharyngeal discomfort, occurred in nearly all patients, consistent with previous reports of extracranial schwannoma, 15 cervical vagal schwannoma, 3 and PPS schwannoma. 2 Moreover, although sympathetic chain schwannomas are reported to show no tumor-induced internal carotid artery (ICA)-internal jugular vein (IJV) or common carotid artery (CCA)-IJV separation in the neck, 24,25 nearly half of the patients (5 of 12 patients; 41.7%) in the present study showed this separation, making the differential diagnosis difficult and confusing.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Diagnostic imaging enabled preoperative diagnosis of schwannoma in all patients; however, accurate preoperative estimation of the nerves of origin was difficult. One reason for this difficulty was the fact that neural paralysis of the involved nerve, which can be a specific subjective symptom, developed in only 1 of the 21 patients (4.8%), whereas nonspecific subjective symptoms, such as cervical mass and pharyngeal discomfort, occurred in nearly all patients, consistent with previous reports of extracranial schwannoma, 15 cervical vagal schwannoma, 3 and PPS schwannoma. 2 Moreover, although sympathetic chain schwannomas are reported to show no tumor-induced internal carotid artery (ICA)-internal jugular vein (IJV) or common carotid artery (CCA)-IJV separation in the neck, 24,25 nearly half of the patients (5 of 12 patients; 41.7%) in the present study showed this separation, making the differential diagnosis difficult and confusing.…”
Section: Discussionsupporting
confidence: 85%
“…However, we could only perform intracapsular enucleation in 7 patients because of an anatomic restriction; the narrow surgical field compared to that in the neck. Complete functional preservation of the nerve of origin was not possible in the patients who underwent intracapsular enucleation, which was inconsistent with the relatively favorable outcomes observed in patients with cervical schwannoma . The most likely reason for this is that the working space for the extirpation procedures is inevitably much tighter in the PPS than in the neck, resulting in increased damage to normal nerve fibers because of the increased pressure, which could not fully recover within the follow‐up period.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations